Telegram - Schevenels, Walther, b. 1894
011-0009-001 F Received at Central Telegraph Office, POST OFFICE OVERSEAS TELEGRAM Official particulars, including Office of Origin + 217 PARIS 33827 31 10 1410= No. Office stamp CITRINE TRADUNIC SOWEST LDN = OPINION J0UHAUX DELEGATION IFTU TO SPAIN URGENT CHARACTER AND NECESSARY BEFORE NEW YEAR THEREFORE SUGGESTS ASKING MERTENS STOP IF PARTICIPATION MERTENS IMPOSSIBLE JOUHAUX ACCEPTS GOING ALONE = SCHEVENELS = Telegrams for all Countries in the world and radio-telegrams for ships on all seas are accepted at all Postal Telegraph Offices or may be telephoned to the Post Office. 27952 11.37. T. 51-443. For free repetition of doubtful words telephone NATIONAL 3383. If the telegram was received by telephone DIAL 559. This form and, if possible, the envelope should accompany any written enquirery. 292/946/11/9